Anticancer drugs: Consumption trends in Spain, prediction of environmental concentrations and potential risks. (October 2017) - Franquet-Griell, Helena; Gómez-Canela, Cristian; Ventura, Francesc; Lacorte, Silvia
Abstract: This study presents the occurrence and impact of 78 anticancer drugs in Spanish river basins based on consumption data in pharmacies during the period 2010–2015 and calculation of the predicted environmental concentrations (PEC). The total consumption of anticancer drugs in Spanish pharmacies was of 23.4 tons in 2015, being mycophenolic acid and hydroxycarbamide the drugs with the highest prescription. Their PECs in river at national scale were up to 80 ng/L. However, the use of different dilution factors revealed major differences between hydrographic basins, and PECriver rose up to 68, 014 ng/L in highly populated rivers with low flows. Concerning acute toxicity, there was no expected risk for the aquatic environment. However, chronic toxicity tests revealed possible long-term mutagenic effects for aquatic organisms. This study provides the tools for the estimation of PEC at river basin scale using time trend consumption data compilation. This information is very useful for prioritization of compounds of concern and permit to focus resources in environmental monitoring and risk evaluation. Graphical abstract: Highlights: 78 anticancer drugs are used in Spain with an annual consumption of 25 tn. Predicted Environmental Concentrations permit prioritization of cytostatic drugs. Mycophenolic acid had the highest predicted concentration at river basin scale. Predicted concentrations and toxicological data permit to assess the risk. Abstract : Predicted Environmental Concentrations calculated from consumption data permits to determine the occurrence and risk of anticancer drugs in waste and river waters.